Investigation of Flat, Hierarchical and Flat – Hierarchical Organisation Structure: Exploring the Challenges and Constraints of Organizational Structures in Educational Institutions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The organizational structure comprises of exercises, for example, task portion, coordination and supervision which are coordinated towards the accomplishment of organizational objectives. The idea of management was perceived many years back by early functional researchers of management, for example, Henri Fayol and Chester Bernard (Koontz, O'Donnell and Weihrich, 1980). Same is seen in momentum results where we see, least satisfaction level among faculty of hierarchical institutes with regards to flexibility in including new modules, new thoughts, basic leadership, industry and abroad interface and degree for advancement.